Elevated plasma levels of IP-10 and MIG are early predictors of loss of control among elite HIV controllers - Poveda, Eva; Fitzgerald, Wendy; Alonso-Domínguez, Jacobo; Aguayo-Arjona, José; Mariño, Ana; Álvarez, Hortensia; Valcarce, Nieves; Pérez, Alexandre; Ruiz-Mateos, Ezequiel; Margolis, Leonid; Lederman, Michael M.; Freeman, Michael L. (Frontiers in Immunology, 2024)
Plasma cytokine levels were quantified among 30 persons with HIV (PWH) identified as elite controllers (15 transient controllers [studied a median of 1.38 years before losing viral control] and 15 persistent controllers). Thirty antiretroviral therapy (ART)-naive PWH, 30 ART-treated PWH with undetectable viremia, and 30 HIV-uninfected controls also were studied. Higher levels of cytokines were recognized among PWH than among controls, with EC displaying the highest levels. Elevated levels of IP-10 and MIG were identified among transient controllers as predictors of the loss of viral control. These findings offer feasible biomarkers for predicting virologic outcome and loss of control in EC.